Mixed-metal thiophosphate CuCd3PS6: an infrared nonlinear optical material activated by its three-in-one tetrahedra-stacking architecture. Issue 15 (1st April 2020) - Li, Zhuang; Zhang, Shengzi; Xing, Wenhao; Guo, Yangwu; Li, Chunxiao; Lin, Zheshuai; Yao, Jiyong; Wu, Yicheng
Abstract : New infrared nonlinear optical material CuCd3 PS6 is activated by its three-in-one tetrahedra-stacking architecture. Abstract : Novel mixed-metal thiophosphate CuCd3 PS6 has been firstly discovered and fully characterized. Careful experimental and theoretical investigations demonstrate that CuCd3 PS6 is a benign infrared nonlinear optical material with a moderate second harmonic generation response of 0.9 × AgGaS2 at 41–74 μm, a large laser damage threshold of 4.1 × AgGaS2, a wide band gap of 2.24 eV and a low melting point of 603 °C. Moreover, first principles calculations indicate that CuCd3 PS6 's intriguing nonlinear optical performance is activated by its three-in-one tetrahedra-stacking architecture.